Implicit Stances Taken by ABC and BBC towards Indonesia Presidential Election: CDA Perspectives - Ahmad Idris Asmaradhani (Journal of English Language Studies, 2019)
In linguistics, stance can be defined as linguistic mechanism used by the speakers/writers to express the feelings, assessments, attitudes, judgments, or commitments about the proposition. This paper is intended to analyze some statements, as the linguistic mechanism, used by ABC and BBC in conveying their stances towards Indonesia Presidential Election. It explores the implicit stances through the uses of lexical choices; nominalization; passivization; and over completeness in the editorials related to (1) the contenders in the election, (2) the uniqueness of the election, (3) the preliminary results: what the contenders said, and (4) issues surrounding the election. Applying van Dijk’s models of CDA to examine the propositions representing the four points in editorials during weeks before and after the election date, analysis was carried out at the selected statements in the texts of their online news. The results showed that the statements constructed by ABC and BBC in the editorials are implicitly taking stances towards a particular side. On the whole, however, most of the statements can be seen as neutral. In terms of van Dijk’s ‘ideological square’ some linguistic features used by ABC and BBC under analyses are dichotomizing one contender into ‘Us’ while the other into ‘Them’ and on the whole as neutral. Based on the novelty of the analysis, prospects for future researches are suggested